Modified CO2 Laser-assisted Sclerectomy Surgery in Chinese Patients With Primary Open-Angle Glaucoma and Pseudoexfoliative Glaucoma: A 2-Year Follow-up Study. Issue 5 (5th May 2020) - Zhang, Yang; Cheng, Gangwei
Abstract : Precis: A modified CO2 laser-assisted sclerectomy surgery (CLASS) based on the characteristics of Chinese eyeball was carried out in Chinese patient and was confirmed to be effective and safe during long-term follow-up. Purpose: The purpose of this study was to study the long-term efficacy and safety of modified CLASS in Chinese patients with primary open-angle and pseudoexfoliative glaucoma. Methods: We enrolled 25 medically uncontrolled primary open-angle and pseudoexfoliative glaucoma patients in this prospective, interventional case series. A combination of modified CLASS and preoperative laser iris management was administered to 29 eyes. Visual acuity, intraocular pressure (IOP), slit-lamp examinations, visual field, and gonioscopy were carried out at baseline and until 24 months postoperatively. Ultrasound biomicroscopy examinations were repeated at 3, 12, and 24 months postsurgically. Results: Mean patient age was 53.92±12.08 years. Mean preoperative IOP was 30.66±10.41 mm Hg; and mean postoperative IOP was 8.17±3.76, and 13.25±2.73, 13.76±2.50, and 13.76±2.50 mm Hg at 1 day, and 6, 12, and 24 months, respectively. Proportional changes in IOP from baseline at 6, 12, and 24 months was 58.33%, 56.25%, and 58.97% ( P <0.001), respectively. Complete postoperative success rates at 12 and 24 months were 62.07% and 48.28%. Qualified success rates at 12 and 24 months postoperatively were both 89.66%. Number of medications administered per patient reduced from 3 at baseline to 0 at 12 and 24 months ( P <0.0001). Two patients demonstrated severe peripheral anterior synechiae (6.90%). Ultrasound biomicroscopy examination revealed a severe scleral lake diminution in 1 patient (3.40%) at 12 months and 2 patients (6.90%) at 24 months. Conclusion: Combination of modified CLASS and preventive laser iris management was effective and safe in the long-term treatment of primary open-angle glaucoma patients.